A young feminist new order: an exploration of why young feminists organise the way they do. Issue 3 (2nd September 2018) - O'Malley, Devi Leiper; Johnson, Ruby
ABSTRACT: This article draws on FRIDA/The Young Feminist Fund's experience of young feminist activism. It explores a range of examples from around the world of how young feminists are reinventing and building different institutions based on new cultures of leadership, greater emphasis on the collective, and more holistic compensation for activist work. These strategies are needed in a world where progressive activism for social justice is under fire: not only from right-wing movements, but also from development that is seen widely as apolitical, yet fails to challenge patriarchal elites who benefit from inequality and poverty.